The Enforcement of Copyright Law in the Field of Music and/or Song in the Framework of Digital Economic Development - Heru Mario; Mompang Lycurgus Panggabean; Rusdin Tahir (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The authorities (government) are obliged to strive to provide legal certainty to their citizens in a practical juridical manner by implementing copyright law enforcement in the field of music and/or songs in the context of developing the digital economy, therefore, in order for these ideals to be achieved, citizens need knowledge of statutory regulations, especially the Law. RI Number 28 of 2014 concerning Copyright. The use of the internet in this digital economic era has increased drastically as evidenced by the rise or development of digital platforms which are mushrooming in Indonesia, apart from providing a good economic impact but also having the impact of violating copyright law, therefore problems arise (1) Is Copyright Law Enforcement in Indonesia based on positive law (Ius constitutum) is in accordance with the principles of justice and the welfare state, and (2) Why protection and fulfillment of copyright for music and/or song creators in the digital economy era must be carried out according to the Pancasila philosophy, and (3) How configuration of music and/or song copyright for the advancement of the digital economy in Indonesia as ius constituendum. This writing uses normative legal research methods, with descriptive research type and uses qualitative data analysis methods. Discussion about law enforcement, especially regarding complaints and differences with reports, what legal problems there are, what the advantages and disadvantages are. This writing will be useful so that the authorities can make new regulations so that in the future regulations will follow developments in the digital economic era